2016
DOI: 10.1002/qj.2808
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical analysis of blocking events: spatial and temporal fluctuations of covariant Lyapunov vectors

Abstract: One of the most relevant weather regimes in the mid-latitudes atmosphere is the persistent deviation from the approximately zonally symmetric jet stream to the emergence of so-called blocking patterns. Such configurations are usually connected to exceptional local stability properties of the flow which come along with an improved local forecast skills during the phenomenon. It is instead extremely hard to predict onset and decay of blockings. Covariant Lyapunov Vectors (CLVs) offer a suitable characterization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 73 publications
(148 reference statements)
6
52
0
Order By: Relevance
“…However, the timing of onset, intensification and decay will be governed by synoptic-scale processes [35,36]. Additionally, Schubert et al [19] suggested that blocked flows were identifiable using Lyapunov exponents and are more unstable and more difficult to predict in their simplified model. This agrees with [2,12], and the results found here show that the Lyapunov exponents were relatively high at onset and intensification.…”
Section: Discussion Summary and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the timing of onset, intensification and decay will be governed by synoptic-scale processes [35,36]. Additionally, Schubert et al [19] suggested that blocked flows were identifiable using Lyapunov exponents and are more unstable and more difficult to predict in their simplified model. This agrees with [2,12], and the results found here show that the Lyapunov exponents were relatively high at onset and intensification.…”
Section: Discussion Summary and Conclusionmentioning
confidence: 99%
“…Although relatively high values of IRE derived from an atmospheric flow field in the study of atmospheric blocking were identified with the onset or demise of blocking events, IRE can also be associated with transitions of the large-scale flow in general, and thus are not exclusive to blocking [12]. Recently [19], however, used covariant Lyapunov vectors to identify blocking flows in a simple channel model with orography. As stated in [19], each covariant Lyapunov vector is associated with a Lyapunov exponent, representing the growth or decay rates in blocked or zonal flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an increase in the finite time LEs (FTLEs) with respect to typical, zonal conditions is attributed to a combination of stronger barotropic and baroclinic conversions, see also an earlier analysis by Frederiksen and Bell (1990). Schubert and Lucarini (2016) interpreted such a counterintuitive finding -blockings are usually thought as being characterized by anomalously high predictability -as resulting from the difficulty of predicting the specific timing of onset (Mauritsen et al 2004) and decay (Quandt et al 2017) of the blocking event. Kwasniok (2018, personal communication) found that atmospheric flows associated with anomalously high values of finite time largest LE resemble correspond to blocked conditions.…”
Section: A Different Mathematical Frameworkmentioning
confidence: 99%
“…More recently methods from dynamical systems theory have been employed. In particular, covariant Lyapunov vectors and unstable periodic orbits were shown to capture blocking events [43,28]. More closely related to our approach of DMD, methods based on the transfer operator, the formal L 2 -adjoint of the Koopman operator, and the behaviour of its point spectrum were used to study transitions to individual blocking event [44].…”
Section: Detecting the Inter-decadal Changes In The North Atlantic Osmentioning
confidence: 99%